2020
DOI: 10.1016/j.jtho.2019.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Circulating Free DNA Using Targeted and Genome-wide Sequencing in Patients with SCLC

Abstract: Introduction: SCLC accounts for approximately 250,000 deaths worldwide each year. Acquisition of adequate tumor biopsy samples is challenging, and liquid biopsies present an alternative option for patient stratification and response monitoring. Methods: We applied whole genome next-generation sequencing to circulating free DNA (cfDNA) from 39 patients with limited-stage (LS) SCLC and 30 patients with extensive-stage SCLC to establish genome-wide copy number aberrations and also performed targeted mutation anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 39 publications
2
68
0
Order By: Relevance
“…In addition, copy number profiling of cfDNA has been used for histological classification of lung tumours [47] and as an early indicator of immunotherapy response [48]. More recently, longitudinal monitoring of genomic copy number from cfDNA in patients with small-cell lung cancer [49], squamous lung cancer [50] and metastatic castration resistant prostate cancer [51] revealed the utility of this approach for early detection of disease progression and identification of genomic events associated with therapy resistance. Longitudinal CNV profiling has also been explored in renal cell carcinoma [52]-a known ctDNA-low malignancy-with limited but promising clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, copy number profiling of cfDNA has been used for histological classification of lung tumours [47] and as an early indicator of immunotherapy response [48]. More recently, longitudinal monitoring of genomic copy number from cfDNA in patients with small-cell lung cancer [49], squamous lung cancer [50] and metastatic castration resistant prostate cancer [51] revealed the utility of this approach for early detection of disease progression and identification of genomic events associated with therapy resistance. Longitudinal CNV profiling has also been explored in renal cell carcinoma [52]-a known ctDNA-low malignancy-with limited but promising clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…Research in Manchester has also looked at the potential for ctDNA to determine therapeutic targets. In this analysis of 39 limited stage and 30 extensive stage SCLC patients, besides TP53 and RB1 alterations, COL22A1, KMT2D and NOTCH1 were found to be commonly mutated [82]. In addition, 85% of patients had a mutation in one of 18 DNA damage repair genes.…”
Section: Circulating Tumour Dna In Small Cell Lung Cancermentioning
confidence: 78%
“…The combination of CTC and ctDNA analysis is of interest, and while it was not performed in this study, it has been demonstrated that collection of CTCs and ctDNA can be performed together using the same blood sample bottle, and this may be of relevance to future clinical utility [83]. TP53 VAF in ctDNA, high VAF and number of CTCs were all significantly related to poor survival [82].…”
Section: Circulating Tumour Dna In Small Cell Lung Cancermentioning
confidence: 89%
“…Interestingly, VAFs were higher in plasma than in tissue (12.04% and 10.80%, respectively) [ 26 ], suggesting the origin of cfDNA might not only be tissue but also CTCs. In another study, TP53 mutation frequency was 79% with greater frequency for advanced small-cell lung cancer (SCLC) than for localized SCLC (83% vs. 76%) [ 56 ]. Furthermore, these mutations were identified in cfDNA at earlier and later tumor stages even when tissue allele frequency was low (~20%).…”
Section: Variability Of Tp53 Status Between Liquid and Solid Biopsmentioning
confidence: 99%
“…Beije et al, 2016 did not find any correlation between presence/absence of CTCs and either cfDNA levels or fragmentation status in colorectal cancer patients [ 59 ], which again might be due to the small sample size analyzed. Regarding lung cancer, a positive correlation was found between TP53 VAF in plasma and CTC counts, being identified as significant predictors of shorter survival [ 56 ].…”
Section: Correlation Of Tp53 Status Between Ctcmentioning
confidence: 99%